Integrating Literature in EFL to Foster Moral Growth and Character Development: A Study of The Jungle Book - Talukder, Md. Jobaar; Hossain Azad, Shahadat (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
Education plays an important role in shaping human character and the selection of appropriate learning materials significantly contributes to students’ personal and moral development. This study attempts to explore the integration of Rudyard Kipling’s The Jungle Book in English as a Foreign Language (EFL) classroom, focusing on its potential to foster moral literacy through ethical sensitivity, logical reasoning, and moral imagination. Using a qualitative descriptive methodology and drawing on Nancy Tuana’s framework of Moral Literacy, the research seeks to examine how the novel’s themes can contribute to the moral growth of the junior high school students. The findings reveal how the ethical sensitivity is conveyed through its themes of brotherhood and acts of heroism, while moral reasoning is exemplified by the emphasis on gratitude and the consequences of revenge. Additionally, the moral imagination is demonstrated through camaraderie and self-preservation efforts. Therefore, the study concludes that The Jungle Book offers valuable material for promoting moral literacy, making it a rich pedagogical resource in EFL contexts. Besides, it emphasizes the dual role of literature in both enhancing language skills and promoting moral values, thereby offering a holistic approach to education that nurtures both linguistic competence and ethical development of the young learners.